Development and Preliminary Validation of a Salah Practice Assessment Instrument for an Islamic Junior High School - Zubaidah, Zubaidah; Muhammad Redha; Salami, Salami; M Nur Akhyar; Suraiya, Suraiya (Jurnal Pendidikan Islam, 2026)
Purpose – This study aimed to develop a prototype salah practice assessment instrument that integrates movements and recitations, assess its preliminary feasibility through expert judgment, and obtain initial responses from Fiqh teachers. Design/methods/approach – This study employed a Research and Development design using a modified 4D model comprising Define, Design, Develop, and limited Disseminate at MTsN 2 Bireuen. The Define stage included teacher interviews, a review of the school instrument, task analysis, and analysis of the Phase D Fiqh curriculum. The prototype contained a blueprint, observation sheet, indicators, rubric, score descriptors, and instructions for use. Feasibility was assessed by two Fiqh subject-matter experts and two evaluation experts, while initial responses were obtained from two Fiqh teachers. The data were analyzed descriptively using percentages. Findings – The assessment by subject-matter experts reached 88.75%, the assessment by evaluation experts reached 86.25%, and the overall mean expert assessment was 87.50%, all of which fell within the highly feasible category. Initial teacher responses reached 81.25% in the strongly agree category. These results indicate preliminary feasibility and acceptance, but do not yet establish construct validity, reliability, classroom practicality, or instrument effectiveness. Originality/Value – The prototype integrates indicators of salah movements and recitations with a rubric and operational score descriptors, thereby extending the school instrument that was reviewed. Practical Implications – The prototype has the potential to assist teachers in assessing salah practice more systematically and transparently. Wider implementation requires product refinement, assessor training, field testing, and validity and reliability testing.